2018
DOI: 10.29252/ijwph.10.4.187
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Powell's Cognitive Rehabilitation with Neurofeedback in Improving Executive Functions, Memory, and Attention to Veterans with Post-Traumatic Stress Disorder

Abstract: Study of sleep quality in chemical-warfare-agents exposed ... [4] Executive function and PTSD ... [5] Gray matter density in limbic and paralimbic ... [6] Neural correlates of emotion regulation ... [7] Caudate volumes in public ... [8] The impact of eye movement and tones on disturbing memories involving ... [9] Evaluation and comparison of executive functions ... [10] The association between complex trauma and ... [11] The role of executive function in posttraumatic ... [12] Executive function in posttraumat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…2). Powell cognitive rehabilitation software was used to measure memory rehabilitation in Sahragard et al (2018). The Powell Cognitive Rehabilitation Protocol was provided to patients in twelve 45-minute sessions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2). Powell cognitive rehabilitation software was used to measure memory rehabilitation in Sahragard et al (2018). The Powell Cognitive Rehabilitation Protocol was provided to patients in twelve 45-minute sessions.…”
Section: Resultsmentioning
confidence: 99%
“…2). Powell cognitive rehabilitation software was used to measure memory rehabilitation in Sahragard et al (2018) Since cognitive rehabilitation interventions, patients with PTSD reported improvements in memory in all four studies.…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation